Women’s Environmental Peacebuilding – from the Lense of Post-Colonial Theological Ecofeminism - Furlan Štante, Nadja (Poligrafi, 2024)
In a broader context, this paper focuses on the need to address environmental issues and include women’s voices and actions in the context of interreligious dialogue—more specifically, to create a venue for women’s engagement in environmental peacebuilding through interreligious encounters and dialogue. First, the phenomenon of religious environmental peacebuilding is introduced as an emerging field that views conflicts over environmental resources (environmental injustice) as an opportunity for the conflicting parties to cooperate with one another and ultimately work toward a lasting and sustainable peace. A brief overview of two examples of good practices of women’s movements for environmental peacebuilding (Navdanya and the Green Belt Movement) and their contributions are briefly analyzed. From this perspective, the question arises: is Western Christian ecotheology listening to the ecotheological perspectives and practices of the Global South? Furthermore, it addresses the importance of including women’s voices and actions (from the Global South and the Global North for mutual enrichment), which are often left out of interreligious dialogue, but could also find their place in religious (environmental) peacebuilding. This paper follows the ecofeminist thesis that the exploitation of the earth (ecological crisis) is closely linked to the marginalization, exploitation, and abuse of women. From this perspective, perceptions and critical perspectives of environmental injustice and the importance of women’s engagement in environmental interreligious peacebuilding are brought together.